The use of pentaploid crosses for durum wheat improvement to Septoria tritici blotch disease resistance and D-genome introgression into durum wheat - Othmeni, Manel (2019)
Pentaploid hybrids derived from crosses between bread wheat (Triticum aestivum) and durum wheat (Triticum turgidum) have the ability to improve the genetic background of either parent by transferring traits of interest. Septoria tritici Blotch (STB) disease is a major wheat problem of durum wheat in the Mediterranean area, especially in Tunisia. Using pentaploid crosses, resistant genes were transferred from three hexaploid wheats, into two susceptible durum wheat genotypes. Stb7/12, Stb6 and Stb17 were found to be ineffective when transferred into durum wheat. However, the segregation of the populations developed for STB disease resistance in field conditions indicated the presence of resistance gene(s) in hexaploid wheat that can be used for durum wheat improvement. Genotyping by sequence analysis of four selected pentaploid populations enabled the quantification of the genetic variability inherited from the bread wheat parent. Results showed that more genetic variability was captured when using the one durum wheat compared to the other, suggesting the importance of the parental choice in pentaploid crosses. The D-genome progenitor of wheat, Ae. tauschii has been used as a source of resistance/tolerance genes to biotic and abiotic stresses, including resistance genes to many fungal diseases of bread wheat. However, only a very few studies have focused on the use of Ae. tauschii for durum wheat improvement. With the aim to develop durum wheat/Ae. tauschii introgression lines, the Langdon 5D (5B) disomic substitution line which lacks the Ph1 gene, was crossed to Ae. tauschii. The F1 amphihaploid was then crossed and backcrossed to the durum wheat “Om Rabiaa 5”. Using a cytogenetic screening approach via GISH and FISH, in combination with D-genome specific SSR markers, tetraploid D-genome introgression lines were identified and characterised. The introgression of D-genome translocations, present in the genetic background of hexaploid/Am. muticum introgression lines, was shown to be an efficient crossing strategy to make use of these D-segments. Translocation were traced via mc-GISH and introgression lines were characterised via mc-FISH. The presence of Am. muticum segment in some of the introgression lines promoted the occurrence of new genomic translocations in the backcross generations to the durum parent. Homozygous D-genome introgressions plus simultaneous homozygous D- and T-genome introgressions were distinguished in a tetraploid background. The D-genome and/or T-genome introgression lines produced will be screened for STB disease resistance as well as other traits of interest.